Correlation of Body Condition Score and Parity in Dairy Cows that Experienced Repeated Breeding in Sendang, Tulungagung - Pristian Devon Martyas Wahyuningrum; Pudji Srianto; Budiarto; Tita Damayanti Lestari; Herry Agoes Hermadi; Erma Safitri (Universitas Airlangga, 2024)
Repeat breeding is a syndrome which affected the reproduction and production efficacy of dairy cattle. Dairy cow is one of an animals which produce milk. This syndrome may cause high economic losses in dairy cattle farm. This research was conducted from February to March 2023. The aim of this research was to determine the correlation of body condition score and parity of repeat breeding on the dairy cow at Tani Wilis Cooperation, Sendang, Tulungagung. A total of 46 dairy cows that contributed to the repeat breeding were used in this study. Sampling was done by purposive sampling with the following condition the date AI and the date of parturition. This research was conducted in a survei with primary and secondary data collection. Primary data retrieval is done by interviewing farmers, body condition score of each dairy cow, and direct observation. As for the secondary data obtained by recording the card Artificial Insemination (AI) owned by inseminator. Data were analyzed using correlate statistics followed by Spearmann Test. The result of the research indicated that no significant difference (P>0,05) in body condition score and parity.